2015
DOI: 10.1080/09712119.2015.1091329
|View full text |Cite
|
Sign up to set email alerts
|

Betaine is a feed enhancer for juvenile grouper (Epinephelus fuscoguttatus) as determined behaviourally

Abstract: The present study aimed to determine if betaine can function as a feeding stimulant or feed enhancer for the juvenile grouper, Epinephelus fuscoguttatus through a behavioural experiment with video recording. Agar gel pellet was used as the medium to deliver the chemical test substances-betaine (BET), amino acids mixture (AAM) and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 17 publications
1
30
1
Order By: Relevance
“…Inclusion of betaine to the AAM did not improve the ingestion rates of the TS pellets despite changes in the ration of betaine and AAM. Such results were in contrast with those reported on brown-marbled grouper Epinephelus fuscoguttatus, where the ingestion rate of the agar gel pellet significantly (P \ 0.05) increased after the inclusion of betaine to the AAM, even in a small portion (Lim et al 2016). Indeed, betaine was also rejected by S. salar as reported by Mearns et al (1987) …”
Section: Resultscontrasting
confidence: 56%
See 2 more Smart Citations
“…Inclusion of betaine to the AAM did not improve the ingestion rates of the TS pellets despite changes in the ration of betaine and AAM. Such results were in contrast with those reported on brown-marbled grouper Epinephelus fuscoguttatus, where the ingestion rate of the agar gel pellet significantly (P \ 0.05) increased after the inclusion of betaine to the AAM, even in a small portion (Lim et al 2016). Indeed, betaine was also rejected by S. salar as reported by Mearns et al (1987) …”
Section: Resultscontrasting
confidence: 56%
“…In this study, the pure agar gel pellet (PAG) was totally rejected by the fish, hence its ingestion rate was 0 %. Therefore, any added test substance which was able to significantly improve the fish ingestion rate on the agar gel pellet can be considered as the potential feeding stimulant (Lim et al 2015;2016). Figure 1 shows the ingestion rates of the juvenile O. marmoratus on different treatments of TS pellet.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive studies with pig (Huang, Xu, Han, & Li, ), broiler (He, Zhao, Dai, Liu, & Bokhari, ; Leng et al., ; McDevitt & Wallis, ) and duck (Wang, Xu, & Feng, ) suggested that dietary betaine supplementation was effective in reducing body lipid deposition. In aquaculture, betaine has long been used as a feed additive to promote fish feeding and growth (Hidaka, Ohsugi, & Kubomatsu, ; Lim, Chor, Tuzan, Shapawi, & Kawamura, ; Rahimabadi, Akbari, Arshadi, & Effatpanah, ; Tırıl, Alagil, Yağci, & Aral, ). However, studies that focus on the food calling property of betaine in different fish species have led to conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…All those ingredients generally contain high fibre content and starch content and these, together with the presence of some antinutritional components, produce limitations to the inclusion of plant ingredients on carnivorous fish diets (Oliva-Teles et al 2015). Also, some CHO sources produce a reduction of feed palatability, which leads to reduce fish intake and growth (Lim et al, 2016) and the presence of antinutritional components such as tannins, oxalates, phytates can produce a reduction on rearing parameters . On the other hand, plant ingredients can be an important source of antioxidant and other bioactive components .…”
Section: Carbohydrate Sourcesmentioning
confidence: 99%